Hospital Staff Perspectives toward Medication Reconciliation: Knowledge, Attitude and Practices at A Tertiary Teaching Hospital in Jordan - Ibrahim, Seliman; Abuhamour, Khawla; Abu Mahfouz, Farah; Hammad, Eman (Jordan Journal of Pharmaceutical Sciences, 2021)
Medicine reconciliation (MedRec) is a patient safety goal. A cross-sectional study using a self-completed questionnaire was conducted at the Jordan University Hospital (JUH) in October- December 2016. A convenient sample of physicians, pharmacists, and nurses was targeted. Statistical analysis was performed to outline the variances across professional groups and factors associated with knowledge, attitude, and practice. Two hundred questionnaires were analyzed of which 41 (20.5%) were completed by physicians, 23 (11.5%) by pharmacists, and 136 (68.0%) by nurses. In total, 162 (81.0%) of the participants responded that they had heard about MedRec before the questionnaire, and139 (69.5%) were aware of the existing policy for MedRec and 143 (71.5%) knew the requirements to complete the MedRec form. Nurses were more likely to know about the MedRec policy and the requirements to complete the MedRec form (p = 0.034 and 0.041 Chi Square, respectively). For 119 (73.5%), working at the JUH was the main source to know about MedRec participants. Level of education appeared significantly to influence knowledge about MedRec. Those holding a postgraduate degree were more likely to know about MedRec 123 (61.5%), p = 0.01, Chi Square test). Moreover, increased years of practice at the JUH significantly influenced knowledge about MedRec (p = 0.04, Mann Whitney test). The MedRec attitude scores median (IQR) was 10 (9-12) indicating supportive views across the study profession groups. None of the variables significantly influenced attitudes toward MedRec. The median (IQR) of MedRec practice was 10 (8-13) representing moderate (62.5%) practice score. MedRec practice scores were significantly affected by profession type (p = 0.00, Kruskal Wallis test). Most often117 (66.8%), the MedRec was completed only upon admission and information about therapy changes were less often recorded compared to patient and medical history details. One third of participants reported they often relied on one source of information, mainly family member or caregiver 117 (66.8%). In conclusion, physicians, nurses and pharmacists in an accredited teaching hospital in Jordan were found to knew about MedRec, policy and form completion requirement. All profession groups showed supported views toward MedRec. However, the practice of MedRec was moderate and physicians followed by nurses were more involved in MedRec steps compared to pharmacists. MedRec often performed upon admission and focus on patient history taking. Practice of MedRec should be enhanced to achieve patient safety centered goals rather than accreditation centered purposes.